2023
DOI: 10.3390/children10010156
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Complication of Thoracic Spine Surgery: Pediatric Horner’s Syndrome after Posterior Vertebral Column Resection—A Case Report

Abstract: Background: Horner’s syndrome (HS) classically consists of the symptom triad of miosis, ptosis, and anhidrosis. It is caused by impairment of a certain pathway in the sympathetic nervous system. It may also appear as part of the clinical signs of other diseases and syndromes, including Pancoast tumors, intradural and/or epidural tumors, thoracic outlet syndrome, syringomyelia, brachial plexus injury, and aortic dissection. Here, we report a very rare complication of vertebral column resection in children, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Moreover, Mohsen Karami et al stated that lumbar or thoracolumbar posterior vertebral resection allows surgeons to correct rigid curves in the pediatric population with minimal risk to nerve roots [ 19 ]. However, some studies have indicated that individuals with operated congenital kyphosis or kyphoscoliosis demonstrate one of the highest rates of neurological deficits post-operatively [ 14 , 20 , 21 , 22 ]. Additionally, Kim et al identified five instances of paraplegia and pseudoarthrosis among 26 cases of significant complications following congenital kyphosis surgery [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Mohsen Karami et al stated that lumbar or thoracolumbar posterior vertebral resection allows surgeons to correct rigid curves in the pediatric population with minimal risk to nerve roots [ 19 ]. However, some studies have indicated that individuals with operated congenital kyphosis or kyphoscoliosis demonstrate one of the highest rates of neurological deficits post-operatively [ 14 , 20 , 21 , 22 ]. Additionally, Kim et al identified five instances of paraplegia and pseudoarthrosis among 26 cases of significant complications following congenital kyphosis surgery [ 8 ].…”
Section: Discussionmentioning
confidence: 99%